A COMPARATIVE HORMONAL STUDY FOR TWO TYPES OF AMNIOTIC ANIMALS - Bakaa H. E; Rashied M. R.; Lina A. Salih (The Iraqi Journal of Agricultural science, 2023)
This research aims to study thyroid hormones, growth hormone, and estrogen hormone in two types of Iraqi amniotes. The study included two types of Mature animals, the local rabbit (Oryctolagus cuniculus), an example of mammals, and the Japanese quail (Coturnix coturnix Japanese), an example of birds. Twenty females were taken from each of the rabbits and quails, and they were of sexual maturity and weighed(1347.2 ± 404.2) g and (173.5 ± 42)g respectively. The level of thyroid function T3, T4, TSH, growth hormones (GH), and estrogen (E2) was measured in the blood serum of quail and local rabbit using ELISA technique following the steps in the leflet kit supplied by the company MY BioSource and CUSABIO. The results of the current study.showed a significant increase in the concentration of T3, T4, TSH, and estrogen hormones in the rabbit compared to the quail at a probability of (p≤0.01). The study also showed a Highly significant increase of growth hormone in rabbit serum compared with the quail at probability of (p≤0.05).